Analisis Minat Belajar Mahasiswa Terhadap Penggunaan Alat Peraga Neraca Cavendish - Muhammad Syahrul Kahar (Universitas Muhammadiyah Sidoarjo, 2017)
The aims of this research are to identify student’s interest in the Cavendish Balance of Aids in physics learning. This research uses Design One Group Pretest-Posttest; Samples used are class D semester I Mathematics Education academic year 2015/2016 of 30 students, Instrument Questionnaire in this study using a questionnaire of student interest. The results showed the use of a aids in the learning of physics effect in to assist students in understanding the material being taught. In addition, the students' interest in learning also improved with the application of visual aids, it can be seen from 96.7% of students stated strongly agree and agree on the statement While 3.3% of students feel disagree with the statement, it is also supported on the value of tcalculate more bigger than ttable with ttable = 2,042 with tcalculate = 20,477. It can be concluded that there is a significant improvement in learning outcomes on the used Cavendish balance of aids so that students' interest in learning becomes better.